Sufism and saint veneration in contemporary Bangladesh: the Maijbhandaris of Chittagong - Harder, Hans (Routledge advances in South Asian studies, 2011)
Focusing on the Maijbhandari movement in Chittagong, south-eastern Bangladesh, which claims the status of the only Sufi order originated in Bengal and which has gained immense popularity in recent years, this book provides a comprehensive picture of an important aspect of contemporary Bengali Islam in the South Asian context.Expertise in South Asian languages and literatures is combined with ethnographic field work and theoretical formulations from a range of disciplines, including cultural anthropology, Islamic studies and religious studies. Analysing the Maijbhandaris tradition of Bengali sp